Resident's assessment of life in Asilo de Molo - Cabrias, Ruby Daryl B.
The objectives of the study is to describe the organizational structure of Asilo de Molo, to know the profile of the elderly residents and to determine whether elderlies' personal assessment of life in Asilo de Molo varies with the means by which they were admitted in the institution.